An association of intrapartum synthetic oxytocin dosing and the odds of developing autism. (August 2020) - Soltys, Stephen M; Scherbel, Jill Rose; Kurian, Joseph R; Diebold, Todd; Wilson, Teresa; Hedden, Lindsay; Groesch, Kathleen; Diaz-Sylvester, Paula L; Botchway, Albert; Campbell, Pamela; Loret de Mola, Julio Ricardo
A case-control study was performed to determine whether an association exists between exposure to synthetic oxytocin and a subsequent autism spectrum disorder diagnosis; 171 children under age 18 meeting Diagnostic and Statistical Manual of Mental Disorders (5th ed.) autism spectrum disorder criteria were compared to 171 children without autism spectrum disorder diagnosis matched by gender, birth year, gestational age, and maternal age at birth. A conditional logistic regression model was used to examine the association of clinical variables and autism spectrum disorder. Significantly elevated odds ratios for autism spectrum disorder were associated with first-time Cesarean section (odds ratio = 2.56), but not a repeat Cesarean section. Odds ratios were also significantly elevated for subjects whose mother's body mass index was 35 or higher at birth (odds ratio = 2.34) and subjects in which the reason for delivery was categorized as "fetal indication" (odds ratio = 2.00). When controlling for these and other variables, the odds of developing autism spectrum disorder were significantly elevated in males with long duration of exposure (odds ratio = 3.48) and high cumulative dose of synthetic oxytocin (odds ratio = 2.79). No significant associations of synthetic oxytocin dosing and autism spectrum disorder were noted in female subjects. The association of elevated autism spectrum disorder odds found with high duration and high cumulative dose synthetic oxytocin in male subjects suggests the need for further investigation to fully elucidate any cause and effect relationship. Lay abstract: Oxytocin is a hormone naturally produced in the human body that can make the womb (uterus) contract during labor. Manufactured oxytocin is frequently given to mothers in labor to strengthen the contractions or in some cases to start labor. This study compared children with a diagnosis of autism and children without autism to see whether children with autism received more oxytocin during labor. The odds of a child having an autism diagnosis were significantly higher if the delivery was a first-time Cesarean section, if the mother had a body mass index of 35 or higher, or if the reason for delivery were a range of fetal problems that made delivery necessary. It was found that boys who were exposed to oxytocin for longer periods of time during labor and received higher total doses of oxytocin had significantly higher odds of developing autism. There were no significant associations of oxytocin dosing and autism noted in female children. As this is the first study to look at any relationship between the dose of oxytocin received during labor and the odds of developing autism, further study needs to be done to determine whether there is any cause and effect relationship. Thus, at this time, there is no recommended change in clinical practice.